2005
DOI: 10.1007/s10641-005-1331-8
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Strategies Explain Genetic Diversity in Atlantic Salmon, Salmo salar

Abstract: SynopsisWe investigated the relationship between conservation status and genetic variability in European and North American Atlantic salmon, Salmo salar, populations, many of which have suffered severe bottlenecks. A negative north-south cline exists for the status of population conservation in this species. A literature review of genetic variability and demographic parameters of wild Atlantic salmon populations resulted in no statistical associations between population conservation status and genetic variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 68 publications
4
32
0
Order By: Relevance
“…In a Pacific salmon hatchery programme, Waples & Do (1994) demonstrated that broodstock practices such as sib-avoidance mating had little permanent effect on the level of inbreeding. This hypothesis is supported by the high levels of heterozygosity we found which is consistent with other small endangered populations at this latitude (Perez et al 1997;Moran & Garcia-Vazquez 1998;Martinez et al 2000;Valiente et al 2005). As the older breeding cohorts are composed mostly of females and the younger (adults, mature parr) mostly of males, high heterozygosities can be explained, at least partially, on the basis of this outbred mating between different cohorts.…”
Section: Discussionsupporting
confidence: 90%
“…In a Pacific salmon hatchery programme, Waples & Do (1994) demonstrated that broodstock practices such as sib-avoidance mating had little permanent effect on the level of inbreeding. This hypothesis is supported by the high levels of heterozygosity we found which is consistent with other small endangered populations at this latitude (Perez et al 1997;Moran & Garcia-Vazquez 1998;Martinez et al 2000;Valiente et al 2005). As the older breeding cohorts are composed mostly of females and the younger (adults, mature parr) mostly of males, high heterozygosities can be explained, at least partially, on the basis of this outbred mating between different cohorts.…”
Section: Discussionsupporting
confidence: 90%
“…Mature male parr reproduction has been speculated to be beneficial for N e (Saunders and Schom 1985;L'Abée-Lund 1989;Martinez et al 2000;Valiente et al 2005;Juanes et al 2007), although mature parr may ''increase'' effective size only in the sense thatN e is increased compared to when mature parr are ignored in analyses (e.g., Jones and Hutchings 2002;Saura et al 2008). Nevertheless, the reasoning implies that parr reproductive contribution increases N e by reducing the variance in (male) individual reproductive success.…”
Section: Discussionmentioning
confidence: 99%
“…Our homing and oceanography scenarios represent opposite extremes of the possible range of behaviours, which in reality are not necessarily mutually exclusive. In the homing scenario, fish were assumed to navigate back to their natal spawning ground from wherever they may have settled and grown up as juveniles, in much the same way as Atlantic salmon return from the ocean to their natal river or even tributary to spawn (Valiente et al, 2005;Verspoor et al, 2002). There was no such navigation behaviour in the oceanography scenario, and newly matured fish simply spawned in the area local to where they had spent their juvenile years.…”
Section: Key Factors Affecting Population Structure and Dynamics Andmentioning
confidence: 99%